Aluminum treatments to control internal phosphorus loading in lakes on Cape Cod, Massachusetts. (3rd April 2017) - Wagner, Kenneth J.; Meringolo, Dominic; Mitchell, David F.; Moran, Elizabeth; Smith, Spence
ABSTRACT: Wagner KJ, Meringolo D, Mitchell DF, Moran E, Smith S. 2017. Aluminum treatments to control internal phosphorus loading in lakes on Cape Cod, Massachusetts. Lake Reserv Manage. 33:171–186. Ten lakes on Cape Cod, Massachusetts have been treated with aluminum since 1995, with 2 of those lakes receiving a second treatment. Elimination of cyanobacterial blooms was the goal in each case. Cape Cod lakes are mostly kettleholes with long detention times. Precipitation and groundwater dominated hydrologic inputs, but internal load contributed a major portion of the total phosphorus (TP) load to treated lakes. Aluminum sulfate and sodium aluminate were used in treatments with the intent to maintain a near-neutral pH in low alkalinity waters. Aluminum doses ranged from 10 to 100 g/m 2, depending on mobile P concentrations in the upper 10 cm of sediment. Results varied, although all treatments lowered TP, provided relief from blooms, increased water clarity, and reduced oxygen demand for multiple years. Important lessons learned over 2 decades include how to apply aluminum to prevent fish mortality, options for dose calculation, and expectations for duration of benefits. To control internal loading and minimize cyanobacterial blooms at the lowest cost, treatment of Cape Cod lakes should apply aluminum at a concentration at least 10 times the mobile P concentration in the upper 10 cm of sediment exposed to anoxia and at concentrations that leave no more than 100 mg/kg of iron-bound P in laboratory inactivation assays. Cost of treatment in 2016 dollars averaged $150/g/m 2 of applied aluminum per ha treated. Aluminum treatment has been demonstrated as a valued lake management tool to improve water quality and reduce nuisance algal blooms in Cape Cod lakes.